Improving Conceptual Understanding of Mechanics through Smartphone-Based Laboratories in Introductory Physics Courses - Laurent, Isabelle (BIRCU, 2013)
Introductory physics courses, particularly mechanics, present persistent conceptual challenges for first-year university students. Many learners enter these courses with deeply rooted misconceptions regarding force, motion, and acceleration that traditional laboratory instruction often fails to address effectively. Recent advances in mobile technology have introduced smartphone-based laboratories as an accessible and cost-effective tool for enhancing inquiry-based learning in physics education. This quasi-experimental study investigates the impact of smartphone-based laboratories on students’ conceptual understanding of mechanics. A total of 128 first-year university students participated in the study and were divided into experimental and control groups. The experimental group engaged in five smartphone-based laboratory activities using the phyphox application, while the control group completed traditional verification laboratories covering the same mechanics topics. Conceptual understanding was measured using the Force Concept Inventory (FCI) administered as pretest and posttest assessments. The results reveal a statistically significant improvement in conceptual understanding among students in the experimental group compared with those in the control group. In addition, students reported positive perceptions regarding engagement, authenticity of experimentation, and relevance to real-world contexts. These findings suggest that smartphone-based laboratories can serve as an effective pedagogical innovation for improving conceptual learning in introductory mechanics courses. The study highlights the potential of integrating mobile technologies into physics education to promote active learning and deeper conceptual comprehension.